2001
DOI: 10.1016/s0005-2728(01)00168-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced changes in the energy coupling and the UCP3 level in rodent skeletal muscles

Abstract: The mechanism of thermoregulatory uncoupling of respiration and phosphorylation in skeletal muscles has been studied. It is found that 24 h cold exposure results in (i) a 3-fold increase in the amount of UCP3 protein in rat skeletal muscle mitochondria, and (ii) pronounced lowering of the membrane potential in isolated rat or mouse skeletal muscle mitochondria. The decrease in membrane potential is reversed by adding bovine serum albumin. Cold exposure is also found to sensitize the membrane potential to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 35 publications
8
35
1
Order By: Relevance
“…3A'), thus suggesting that, under this experimental condition, PUCP may be insensitive to ATP in DWM from stressed seedlings (see also Trono et al 2006). At this regard, lower UCP sensitivity to nucleotides as a result of stress has been already observed in mitochondria from cold-stressed rat skeletal muscle (Simonyan et al 2001) and dehydrated slices of Jerusalem artichoke tubers (Paventi et al 2006). In the light of this, it appears unlikely that any change of ATP concentration occurring under stress conditions may modulate PUCP, whereas one can assume that the loss of sensitivity to ATP is the key factor for PUCP activation.…”
Section: Determination Of Cef-atp Contentmentioning
confidence: 72%
“…3A'), thus suggesting that, under this experimental condition, PUCP may be insensitive to ATP in DWM from stressed seedlings (see also Trono et al 2006). At this regard, lower UCP sensitivity to nucleotides as a result of stress has been already observed in mitochondria from cold-stressed rat skeletal muscle (Simonyan et al 2001) and dehydrated slices of Jerusalem artichoke tubers (Paventi et al 2006). In the light of this, it appears unlikely that any change of ATP concentration occurring under stress conditions may modulate PUCP, whereas one can assume that the loss of sensitivity to ATP is the key factor for PUCP activation.…”
Section: Determination Of Cef-atp Contentmentioning
confidence: 72%
“…It is possible that this thermogenesis is caused by an increased amount of UCP3 that, through its uncoupling action, is responsible for the heat production. Indeed, it has consistently been found that acute hyperthyroidism is associated with an increased level of UCP3 mRNA and UCP3 protein in muscle (Gong et al 1997;Larkin et al 1997;Lanni et al 1999;Barbe et al 2001;de Lange et al 2001;Short et al 2001;Simonyan et al 2001), and there is evidence of altered mitochondrial parameters (increased mitochondrial membrane permeability, i.e. 'uncoupling') in muscle mitochondria from hyperthyroid animals (Lanni et al 1999;de Lange et al 2001).…”
Section: Ucp2/ucp3 Are the Mediators Of Thyroid Thermogenesismentioning
confidence: 99%
“…A natural candidate for such a role would be OE itself, which is well known as a weak mitochondrial uncoupler (34). To test this hypothesis, we titrated mitochondrial membrane potential in the control and OE-exposed permeabilized MIN6 cells with OE (35,36). Typical titration kinetics (Fig.…”
Section: Effect Of Oleate Exposure On Insulin Secretion-incubationmentioning
confidence: 99%